Avenanthramide concentrations in developing oat genotypes as influenced by crown rust - Peterson, David M.; Dimberg, Lena H. (MTT, 2004)
Oat (Avena sativa L.) avenanthramides are unique antioxidant compounds found constitutively in mature grain and inducible in seedling leaves by crown rust (Puccinia coronata Corda. var. avenae W.P. Fraser & Ledingham) spores in incompatible host-parasite reactions. We investigated the pattern of avenanthramide accumulation in developing grain and the effects of natural infestations of crown rust on the concentrations of avenanthramides in leaves and grain. Nine genotypes that varied from susceptible to resistant for crown rust were grown in the field in Madison, Wisconsin in 2001 and exposed to a substantial natural occurrence of rust spores. Leaves and grain were harvested and analyzed for avenanthramide concentrations at intervals from panicle emergence to maturity. The experiment was repeated in 2002 with six genotypes. An additional variable was treatment with the fungicide, Tilt. In 2001, avenanthramides accumulated in grain during filling and in leaves between panicle emergence and senescence. Avenanthramide concentrations differed significantly among genotypes in both tissues. The two genotypes most resistant to crown rust, Belle and X7571-1, had the highest leaf avenanthramide concentrations, although crown rust score was not correlated with leaf (or grain) avenanthramide concentration across all nine genotypes. Rust infestation was almost nil in 2002. Belle and X7571-1 had lower leaf avenanthramide concentrations than in 2001, while other less resistant genotypes were similar both years. This suggested that the infestation of crown rust spores in 2001 had induced higher avenanthramide concentrations in the most resistant genotypes. Tilt treatments lowered avenanthramide concentrations in leaves of all genotypes and had no effect on concentrations in the grain. The results suggest that avenanthramides may function as phytoalexins in some genotypes but not in others.
Keywords: Ka; avenanthramides; crown rust; phytoalexins; leaf; grain